The art more geometrico: Emotions, measure, and mixed art forms in Plato - Maggi, Claudia (Revista Archai, 2025)
The aim of this paper is to present some aspects of the correlation between tragedy and comedy from some passages of Platonic dialogues, in order to show that this connection goes back to at least two issues: the cultural background, on which the dialogues depend, where such contaminations between tragedy and comedy are attested; Platonic intent to clarify the psychological and ontological causes of the mixture of pleasure and pain, and to evaluate the dramaturgy from this causal investigation. In such a framework, there are some hints at the possibility of a philosophical drama, where problems of popular art are avoided, thanks to knowledge of both the structure of reality and that of the soul.